Les Dessins trans-conscients de Stéphane Mallarmé par Ernest Fraenkel : une méthode originale - Anna Samson; Serge Chamchinov (Continents manuscrits)
This article focuses on the improvisation process, both graphic and linguistic, developed in 1952 and 1960 by Ernest Fraenkel on Un Coup de dés jamais n’abolira le hasard (1897, 1914), by Stéphane Mallarmé, and then developed, almost simultaneously in 1968 and 1969, in the artists’ books of Mario Diacono and Marcel Broodthaers. The authors propose a presentation of Fraenkel’s method based on his book Les Dessins trans-conscients de Stéphane Mallarmé (1960) and an observation of the history of the critical and artistic reception of that book. They explain the originality of the conception of that book and its role in the development of the tradition of the artist’s book in France.